Social inclusion through para sport: A critical reflection on the current state of play - Bantjes, J.; Swartz, L. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Medicine has played an integral role in both the inception and development of the Paralympic Games. Sports physicians are well positioned to continue to influence the development of the paralympic movement and to help focus the movement on its agenda to promote social inclusion. This article looks critically at some of the key challenges that the paralympic movement faces in its quest to promote social inclusion, and considers the role of sports medicine in this process.